2016
DOI: 10.1007/s00289-016-1642-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing properties of epoxy resins with poly(ε-caprolactone) healing agent

Abstract: Abstract:Thermally induced healing through thermoplastic poly(ε-caprolactone) (PCL), dissolved in 12.5, 25, 37.5 and 50 wt.%, respectively, in amine cured epoxy resins (EPs) was studied on compact tension (CT) specimens. Aromatic (hydrogenated diglycidyl ether of bisphenol A-type) and aliphatic (glyceroltriglycidylether) EPs were cured with the same amine (Jeffamine D 230) to receive EPs with different glass transition temperatures (Tg). Tg values of the parent EPs were lower (Tg= 32 o C) and higher (Tg= 90 o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 15 publications
4
43
0
Order By: Relevance
“…Healing occurs via chain entanglement of the PCL molecules above the T m . Not surprisingly, semi-IPN structured EP/PCL outperformed EP variants with dispersed PCL phase with respect to healing [9]. Note that all the above information is related to EP/PCL modified in the bulk.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Healing occurs via chain entanglement of the PCL molecules above the T m . Not surprisingly, semi-IPN structured EP/PCL outperformed EP variants with dispersed PCL phase with respect to healing [9]. Note that all the above information is related to EP/PCL modified in the bulk.…”
Section: Introductionmentioning
confidence: 80%
“…The related structure can be termed as quasi (with the nanoweb) or real semi-interpenetrating network (semi-IPN) because the thermoplastic phase is also continuous. It was also reported that thermoplastic PCL may work as a healing agent in EPs [9]. Healing occurs via chain entanglement of the PCL molecules above the T m .…”
Section: Introductionmentioning
confidence: 95%
“…PCL finds wide application in biodegradable packaging, in sutures, in adhesives, in non-woven fabrics or for the production of synthetic leather and dressings [32]. One of the most recent applications of PCL is as blending agent in epoxy system for self-healing applications [7,37,38].Self-healing capability, intended as the ability to repair damages and restoring partially or completely the lost properties and functions, has been already demonstrated in many types of polymers [39] including thermoplastics, elastomers, and thermosets [40]. Generally speaking, the self-healing mechanism can be summarized in three principal steps: actuation of self-healing feature, transportation of healing agent or chemicals in the damaged zone, final chemical or physical reparation [41].…”
mentioning
confidence: 99%
“…Generally speaking, the self-healing mechanism can be summarized in three principal steps: actuation of self-healing feature, transportation of healing agent or chemicals in the damaged zone, final chemical or physical reparation [41]. Thermoplastic polymers have demonstrated an ability to heal after heating above their melting temperature by molecular re-entanglement processes across the broken surfaces [38]. However, even if their repairing mechanism is quite easy, they were considered less interesting than thermosets when high thermal stability and solvent resistance are required.…”
mentioning
confidence: 99%
See 1 more Smart Citation